(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2018)
This article is based on the involvement of the author during the last 3 years (2016-2018) in community actions and interventions where processes for social change are promoted in favor of equity and gender equality, therefore the title: «Deconstructing hegemonic masculinities - a means for the prevention of gender-based violence». It aims to rescue some elements extracted from the experience of working with men of different ages, who have had to assume challenges to achieve real changes that contribute to the development of themselves, their companions, families and community spaces. The purpose of this research article is to make known the importance of working with men to promote awareness, gender awareness, this to gestate consequent changes in the relationships of men with their families, promoting nonviolence and healthy affectivity ; To this end, actions must be carried out that question mandates assigned by the same society in which power relations favor men, consequently relegating women to situations of violence and submission. The subject has been approached from the holistic-anthropological approach, with its own methods such as ethnography and particular techniques of science such as direct and participant observation, application of open and in-depth interviews.